Height-for-age in Children under 5 Years Old with Down Syndrome and Hypothyroidism - Muhammad Faizi; Nur Rochmah; Yuni Hisbiyah; Anang Endaryanto; Soetjipto (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Children with Down syndrome tend to have accompanying comorbidities, such as hypothyroidism, and late detection of this ailment leads to reduced growth of the child. This study aimed to assess the growth patterns in children with Down Syndrome and hypothyroidism at diagnosis.Methods: This cross-sectional study was conducted from September to December 2020 with 56 subjects at the Pediatric Endocrine Outpatient Clinic of Dr. Soetomo Hospital. Diagnosis of Down Syndrome was confirmed by karyotyping, while the weights and heights were assessed using a standardized curve for children with Down Syndrome and then calculated using Peditools. Fifty-six children with Down Syndrome and hypothyroidism were included, comprising 32 boys and 24 girls (mean age, 37.75 ± 34.26 months). Majority of the subjects had normal weight, height, and Body Mass Index (36/56 [mean z-score, −1.62 ± 2.36], 33/56 [mean height-z-score, −0.43 ± 2.74], and 30/56 [mean z-score, −2.00 ± 2.06], respectively). Furthermore, the mean onset of diagnosis was 17.07 ± 32.23 months, where 23 out of the 56 children had short stature and had gotten diagnosed at over 12 months of age.Conclusion: From the results obtained, hypothyroidism can be said to be associated with reduced growth in children with DS.